Some proposals for a new practicum model in the Faculty of Education Toledo - Olga Elwes Aguilar; Ricardo Fernández Muñoz; Begoña Rivas Rebaque (Universitat Politècnica de València, 2012)
Come into effect the new Curriculum for the specialities of Infant Teacher Education and Primary Teacher Education for the ESHE, we meet the challenge to turn the old titles of Graduate in Teacher Training (along with their corresponding specialities) into the current framework of the Teaching Degree. The transformation not only involved the implementation of one additional academic year but the revision, configuration and  reconsideration of the subjetcs.  From the point of view of the teacher training for the future profession, changes have been implemented caused fundamentally by considering the importance of integrating theory and practice within initial formation of the teachers.   We have three aims in the present paper: first of all, to raise organization and administration of the new model. Then, we will present a teaching supervision with a blended learning approach through the virtual campus of the University of Castilla-La Mancha, and, finally, we will share some reflections from student's experience as a real agent and protagonist in this dynamic process.